Rancangan Pelaporan Security Check Point Berbasis Digital pada Unit Aviation Security (AVSEC) di BLU UPBU Kelas I Bandar Udara Aji Pangeran Tumenggung Pranoto Samarinda - Ramadhani, Alfiyyah Nur; Wahyudono, Wahyudono; Adriansyah, Feri (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
This study addresses the inefficiencies of manual logbook reporting within the Aviation Security (Avsec) Unit at Aji Pangeran Tumenggung Pranoto Airport, Samarinda, where the existing paper-based system for daily activities, random checks, checklist patrols, and found items is hindering efficiency due to printing requirements, data vulnerability, and limited accessibility. To overcome these challenges, an innovative digital reporting system utilizing Google Spreadsheet has been implemented, allowing all Avsec personnel to input data digitally via Google Forms, with administrative access to the central spreadsheet ensuring data security and organized record-keeping. This digital transformation significantly boosts Avsec performance by streamlining data input, enhancing supervision, and improving the accuracy of activity recording for both administrators and users, thereby aligning with the core purpose of information technology to facilitate tasks and manage data swiftly and accurately for enhanced security and comfort in air travel.